Inhibition of Cell Cycle and Induction of Apoptosis y Ethanol Leaves Extract of Chrysanthemum cinerariifolium (Trev.) In T47D Breast Cancer Cells - Roihatul Mutiah; Alfiyah Laily Inayatin; Rahmi Annisa; Yen Yen Ari Indrawijaya; Anik Listiyana (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
Chrysanthemum cinerariifolium (C.cinerariifolium) is a plant of the Asteraceae family, which has been applied by the community as an ornamental plant and traditional medicine. In this study, the effect of C. cinerariifolium leaves extract on inhibition of cell cycle and induction of apoptosis in T47D breast cancer cells was tested and compared to the standard chemotherapy agent. The citotoxic activity of C. cinerariifolium leaves extract against T47D cancer cells and Vero normal cells was tested by MTT method. Profile of apoptosis and cell cycle were observed by flow cytometry method. Based on chemical compounds profil which is tested used TLC showed that C.cinerariifolium leaves extracts contained flavonoid and terpenoid chemical compounds. The result of cytotoxic test showed that leaves extract of C. cinerariifolium was able to inhibit the growth of T47D cancer cell at IC50 418.8μg/mL. Doxorubicin, extracted from Streptomyces peucetius used as treatment in several cancers including breast cancer. Doxorubicin could inhibit the growth of T47D cancer cells in 115.1μg/mL. The results of cell cycle analysis showed that the C. cinerariifolium leaves extract inhibited cell cycle in G0-G1 and S phase, whereas doxorubicin was able to inhibit cell cycle in G0-G1 phase but experienced cell accumulation in G2-M phase. The percentage of apoptosis in cycle was showed in M1 (sub G1) and M5 (multinuclear) phase which treatment of C. cinerariifolium leaves extract was higher than doxorubicin. Therefore, C. cinerariifolium leaves extract has potential activity as anticancer agent causes inhibition of cell cycle and induction apoptosis.